Using Duolingo Helps Improve English Vocabulary - Siti Syaripah; Raihan Nurrahman; Juliana Rahma Amelia; Cici Situmorang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This articel aims to contribution to aplication Duolingo in process learning English in the digital age, especially in strengthening English vocabulary mastery, which is the main foundation. English language skills are very important in today's era as a global language that influences the fields of education, technology, and international communication. Vocabulary serves as a fundamental element in mastering English among the four main skills, namely Listening, Speaking, Writing, and Reading. The Duolingo application, as a digital learning platform, offers exercises through game methods such as multiple choice, translation, and pronunciation exercises that are easy to master. This articel applies a quantitative method employing Partial Least Squares-Structural Equation Modeling (PLS-SM) supported by SmartPLS 3.0 software. Data were obtained through survey observations by distributing questionnaires to PGSD students at Institut Prima Bangsa. The variables analyzed in this study were use the aplication Duolingo (x) and the improvement of English vocabulary (y). The research shows that use Duolingo application had a positive effect on the improvement of English vocabulary among PGSD students at the Prima Bangsa Institute. The outcomes concerning validity and reliability tests showed that the concepts of Duolingo Application Use and English Vocabulary Improvement had a Composite Reliability value of more than 0.70, yeild results these constructs were valid and reliable.